Strategi Pemasaran Bisnis Budidaya Ikan Lele “Berkah Mandiri” Perspektif Etika Bisnis Islam - Nur Laila, Mufidatun; Fuadilah Habib, Muhammad Alhada (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Catfish cultivation has great potential in this era because it is popular with the public, so quite a lot of new catfish cultivation businesses have emerged. This causes the world of catfish buying and selling business to have increasingly fierce competition, so it requires a good marketing strategy to be able to win the competition in the catfish farming business sector. Preliminary survey results found that implementing a marketing mix strategy was able to increase sales of Berkah Mandiri catfish. The purpose of this research is to describe the Marketing Strategy for the Berkah Mandiri Catfish Cultivation Business from an Islamic Business Ethics Perspective which is proven to be able to increase sales. This research uses a qualitative descriptive research type. Data collection techniques include interviews, observation and documentation, then data analysis is carried out. Data analysis which includes the stages of data condensation, data presentation and drawing conclusions. The results of the research found that the Berkah Mandiri catfish farming business succeeded in increasing sales with the 7P marketing mix strategy (product, price, place, promotion, people, processes and physical evidence) in the form of selling good quality and healthy catfish of various types, providing price based on fish quality and negotiable selling price, easy to reach location, opening a sales stand in the market, having a suitable environment for cultivation, promoting by word of mouth and social media (WhatsApp and Facebook), skilled human resources with a high work ethic , choosing superior catfish seeds, providing good catfish feed, paying attention to the quality of the pond water, handling pests and diseases, the fish harvesting process is in accordance with safe harvest procedures, the pond is cleaned once a week, the size of the pond is divided into several sizes ( according to the age of the fish) and the pond looks clean. There are 5 principles of Islamic Business Ethics that are applied, namely; honest and trustworthy, accurate in weighing and avoiding gharar, mutually beneficial, voluntary in buying and selling and not badmouthing other people's business. Keywords: Marketing Strategy, 7P Marketing Mix Strategy, Islamic Business Ethics